Urine non-contact sensor that evaluates multiple urination using capacitance change to inform when to replace inner diaper - Shichitani, Keisuke; Nakajima, Kazuki (Frontiers in Digital Health, 2025)
IntroductionUsing the toilet to excrete is important, which is a matter of human dignity. However, incontinent and bedridden elderly people who are unable to go to the toilet use disposable adult diapers. In this study, we developed a diaper sensor system that uses capacitance changes to quantitatively evaluate the volume of urine absorbed by diapers from different manufacturers and different approximate numbers of absorption (ANA) and to inform caregivers when to replace diapers.MethodsThree experiments, α: comparative verification by urination pattern, β: effect of ANA, and γ: evaluation by each diaper manufacturer, were conducted using a plastic torso filled with saline as a phantom. In addition, examine the actual urination time and urine absorption volume when the human wears a diaper; one volunteer wore inner and outer diapers, and pseudo-urine was infused via a tube.ResultsOverall, the results indicate that the accuracy of urine absorption volume estimation showed that the pattern of multiple infusions followed that of a single infusion.DiscussionThe results confirm that the diaper sensor system is highly versatile and independent of the urination pattern and diaper manufacturer. If the diaper sensor system is put into practical use, it is expected to provide quantitative information on when to replace diapers.